(untitled) (JOYCED: Journal of Early Childhood Education, 2025)
Character is one of the important things that must be formed from an early age. The formation of character in children does not occur spontaneously, there is a process that is passed through stimulation. One of the characters that must be formed is responsibility. This study aims to determine the habit of praying Ashar in congregation in improving the character of responsibility of early childhood at TPQ Darul Muttaqin, Buayan District. The method used is a descriptive qualitative approach with observation, interview, and documentation. The subjects of this study were male and female students of TPQ Daarul Muttaqin Buayan Kebumen. The results of the study showed that the habit of praying Ashar in congregation is carried out every Monday, Tuesday, Wednesday, Thursday, and Saturday routinely. The habit of praying in congregation also forms an attitude of discipline, independence, and responsibility in children. Children begin to get used to coming on time for congregational prayers, performing ablution independently, getting used to queuing and tidying up their own prayer equipment. This activity also encourages children to have a sense of social responsibility, such as reminding friends to join in ablution. The conclusion of this study is that the habit of praying in congregation is an effective strategy in forming a character of responsibility in early childhood.